Mild chemical pretreatments are sufficient for complete saccharification of steam-exploded residues and high ethanol production in desirable wheat accessions. (November 2017) - Zahoor,; Tu, Yuanyuan; Wang, Lingqiang; Xia, Tao; Sun, Dan; Zhou, Shiguang; Wang, Yanting; Li, Ying; Zhang, Heping; Zhang, Tong; Madadi, Meysam; Peng, Liangcai
Graphical abstract: Highlights: Four wheat accessions are distinctive at wall polymer extraction by steam explosion. It performed a combined pretreatment of steam explosion with dilute acid or alkali. With 1% Tween-80, Talq90 and Talq16 accessions showed a complete enzymatic hydrolysis. Talq90 and Talq16 also exhibited the highest bioethanol yields at 18.5%–19.4%. Talq90 and Talq16 had improved polymer features in raw and steam-exploded residues. Abstract: In this study, a combined pretreatment was performed in four wheat accessions using steam explosion followed with different concentrations of H2 SO4 or NaOH, leading to increased hexoses yields by 3–6 folds from enzymatic hydrolysis. Further co-supplied with 1% Tween-80, Talq90 and Talq16 accessions exhibited an almost complete enzymatic saccharification of steam-exploded (SE) residues after 0.5% H2 SO4 or 1% NaOH pretreatment, with the highest bioethanol yields at 18.5%–19.4%, compared with previous reports about wheat bioethanol yields at 11%–17% obtained under relatively strong pretreatment conditions. Furthermore, chemical analysis indicated that much enhanced saccharification in Talq90 and Talq16 may be partially due to their relatively low cellulose CrI and DP values and high hemicellulose Ara and H-monomer levels in raw materials and SE residues. Hence, this study has not only demonstrated a mild pretreatment technology for a complete saccharification, but it has also obtained the high ethanol production in desirable wheat accessions.